Old Dubrovnik, Young Serbia and Vague Croatia : Mental Maps in the Serb-Catholic Imagination in Dubrovnik - Czerwiński, Maciej (1976– ) (Instytut Historii PAN, 2020)
This article describes the experience of the community of Serb-Catholics living in Dubrovnik in the early twentieth century. It is based primarily on an investigation of the literary and cultural periodical Srdj (1902–08). This study focuses, firstly, on the conceptual ambivalence resulting from efforts to apply linguistic criteria to determine Serbian identity and, secondly, on the efforts to construct a mental map that would serve projections of Serbian symbolic territory. While the presence of the Serb-Catholic milieu in the city was short-lived (from the mid-nineteenth century to the First World War), it nevertheless left traces on the urban landscape that typified the ambivalent formation of national identity along religious lines, as Croatians were associated with Catholicism and Serbs with Orthodoxy.
s. 143-160
Keywords: Dubrownik (Chorwacja) -- historia [KABA]; Dalmacja (Chorwacja; region) -- stosunki międzyetniczne -- 19 w. [KABA]; Serbowie - Chorwacja - Dubrownik - historia; Dubrownik (Chorwacja) - stosunki międzyetniczne